Evaluation of Sterility of Saline Formulations Manufactured for Wound Care in Veterinary Practice - Madyson Marcolina; Zoë J. Williams; Dean Hendrickson; Lynn M. Pezzanite (Veterinary Sciences)
The discontinuation of commercially available saline and hypertonic saline wound dressings for the veterinary market has restricted options available to veterinary practitioners treating contaminated and infected wounds. Clinicians may manufacture their own homemade solutions in clinics or field settings to treat equine or livestock species; however, information is limited on whether autoclave sterilization is necessary or sufficient to eliminate bacterial growth in isotonic and concentrated salt solutions and how long they may subsequently be stored prior to use. The purpose of this study was to assess sterility of saline (0.9%) and hypertonic saline (20%) solutions manufactured three ways (1—autoclaved glass bottle that was autoclaved again following solution preparation; 2—autoclaved glass bottle, not autoclaved again following preparation; 3—non-autoclaved plastic bottle, not autoclaved following preparation). Solutions were stored two different ways (1—solution in sealed bottle or 2—soaked gauze in vacuum-sealed plastic packets). Products were assessed for bacterial growth at four time points (baseline, one week, one month, six months). At each time point, samples of each solution were plated on Luria–Bertani (LB) agar plates and assessed for bacterial growth at 24 h. Vacuum-sealed soaked gauze was placed in antibiotic-free growth media for 24 h, and then media were plated on LB agar plates and assessed for bacterial growth at 24 h. If bacterial growth was detected, qualitative culture with sensitivity was performed to identify bacterial isolates. No bacterial growth was detected in stored solutions for any preparation method, concentration or time point assessed. Bacterial growth was detected from 0.9% saline-soaked gauze at 1 week, 1 month and 6 months in all container types for at least one time point. Bacterial culture revealed Ralstonia, Bacillus, Sphingomonas and Staphylococcus species. Environmental controls (water, containers, salt, biosafety cabinet and benchtop) were submitted for culture to identify the source of contamination, yielding light mixed growth from tap water and no growth from any other locations. These findings provide clinicians with practical information to guide preparation and storage of homemade saline-based products for wound care.